Pengaruh Perputaran Modal Kerja, Likuiditas, Dan Leverage Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Studi Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023) - Citra, Yulia; Amaniyah, Evaliati (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This reìseìarch aims to deìteìrmineì and analyzeì theì eìffeìct of working capital tuìrnoveìr, liquìidity and leìveìrageì on company valuìeì with profitability as an inteìrveìning variableì in food and beìveìrageì companieìs listeìd on theì Indoneìsia Stock Eìxchangeì for theì 2019-2023 peìriod. Theì meìthod uìseìd was a puìrposiveì sampling meìthod and 12 companieìs weìreì obtaineìd. Theì teìchniquìeì uìseìd in this reìseìarch is muìltipleì lineìar reìgreìssion analysis and uìseìs quìantitativeì data. Baseìd on theì reìseìarch reìsuìlts, it shows that: 1) working capital tuìrnoveìr has a neìgativeì and significant eìffeìct on company valuìeì; 2) Liquìidity has a positiveì and insignificant eìffeìct on company valuìeì, 3) Leìveìrageì has a neìgativeì and significant eìffeìct on company valuìeì 4) working capital tuìrnoveìr, liquìidity and leìveìrageì areì ableì to meìdiateì company valuìeì throuìgh profitability